Khitan Perempuan Dalam Pandangan Fiqh, Budaya dan Female Genital Mutilation (FGM) - Rohmah Maulidia (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2009)
This study aims to examine the practice of female circumcision from three perspectives: Islamic fiqh, local culture, and the international approach known as Female Genital Mutilation (FGM). This study uses a qualitative method with a multidisciplinary approach, through a literature review of classical and contemporary fiqh, cultural anthropology, and international documents. The results showed that in fiqh, female circumcision has different legal statuses depending on the school of thought, ranging from obligatory to sunnah or permissible. On the other hand, cultural practices are often mixed with elements of patriarchal tradition without a strong medical basis. Meanwhile, FGM is globally condemned as it is considered harmful to women's health. This study emphasizes the importance of distinguishing between religious teachings and harmful cultural practices, as well as the need for an educational and contextual approach in responding to this issue.